Income diversification in Zimbabwe: welfare implications from urban and rural areas - Ersado, Lire (International Food Policy Research Institute, 2003)
The paper examines, taking into account the urban-rural divides, the changes and welfare implications of income diversification in Zimbabwe following macroeconomic policy changes and droughts of the early 1990s. Data from two comparable national income, consumption, and expenditure surveys in 1990/91 and 1995/96 show that the percentage of households earning income from private and informal sources grew considerably while that from government and formal sources declined. In general, rural households tend to have a more diversified portfolio of income compared to urban and the degree of income diversification decreases with the level of urbanization. However, there are important differences in the level of diversification within the rural and urban areas, depending on wealth: while the relatively better-off households have a more diversified income base in rural areas, it is the poor that pursue multiple income sources in urban areas. A decomposition of changes in welfare indicates that the total contribution of income diversification is large and increased between 1990/91 and 1995/96 in both urban and rural areas. On the other hand, there were significant declines in returns to human and physical capital assets during the same period. The findings suggest that households with a more diversified income base are better able to withstand the unfavorable impacts of the policy changes and weather shocks. The fact that relatively better-off households have a more diversified income base following the shocks implies that the poor are more vulnerable to economic changes unaccompanied by well-designed safety nets.